ANALISIS YURIDIS BESARAN SIMPANAN PESERTA TAPERA BERDASARKAN PERATURAN PEMERINTAH TENTANG PENYELENGGARAAN TABUNGAN PERUMAHAN RAKYAT - Rasendryo Wahyu Ramadhanianto; Lutfian Ubaidillah (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
This research analyzes the Indonesian government's policy regarding the amount of savings for Public Housing Savings (Tapera) participants based on Government Regulation Number 21 of 2024 concerning Amendments to Government Regulation Number 25 of 2020. This research uses a regulatory and conceptual approach, as well as a normative type of research. The Tapera policy aims to provide low-cost, long-term funds to meet the community's adequate housing needs. However, the contribution amount of 3% of salary, which is 2.5% borne by workers and 0.5% by employers, is considered burdensome for workers. In addition, Tapera benefits are limited to owning, building or repairing a first home, which creates benefits for participants. The research results show that this policy, although well-intentioned, does not fully take into account the additional burden on low-fatality workers and is not commensurate with the expected benefits. The government needs to review the amount of contributions and improve the Tapera management mechanism to ensure fairer and more equitable benefits for all participants.